Gastric Electrical Stimulation for the Treatment of Obesity: From Entrainment to Bezoars—A Functional Review. (14th January 2013) - Mintchev, Martin P.
Abstract : Growing worldwide obesity epidemic has prompted the development of two main treatment streams: (a) conservative approaches and (b) invasive techniques. However, only invasive surgical methods have delivered significant and sustainable benefits. Therefore, contemporary research exploration has focused on the development of minimally invasive gastric manipulation methods featuring a safe but reliable and long-term sustainable weight loss effect similar to the one delivered by bariatric surgeries. This antiobesity approach is based on placing external devices in the stomach ranging from electrodes for gastric electrical stimulation to temporary intraluminal bezoars for gastric volume displacement for a predetermined amount of time. The present paper examines the evolution of these techniques from invasively implantable units to completely noninvasive patient-controllable implements, from a functional, rather than from the traditional, parametric point of view. Comparative discussion over the available pilot and clinical studies related to gastric electrical stimulation outlines the promises and the fallacies of this concept as a reliable alternative anti-obesity strategy.